Rhizobacteria Communities of Phytoremediation Plant Species in Petroleum Hydrocarbon Contaminated Soil of the Sudd Ecosystem, South Sudan - J. A. Ruley; J. B. Tumuhairwe; A. Amoding; O. T. Westengen; H. Vinje (International Journal of Microbiology)
The Sudd wetland is one of the oil-rich regions of South Sudan where environmental pollution resulting from oil extraction activities has been unprecedented. Although phytoremediation is the most feasible technique, its efficacy reduces at high TPH concentration in soil. This has made rhizoremediation the most preferred approach. Rhizoremediation involves use of a combination of phytoremediation and biostimulation. The process is catalyzed by the action of rhizobacteria. Therefore, the objective of this study is to characterize rhizobacteria communities prevalent in phytoremediation species growing in hydrocarbon-contaminated soils biostimulated with cattle manure. The treatments studied were plant species only (T1), plant species and hydrocarbons (T2), plant species and manure (T3), and plant species, manure, and hydrocarbons (T4). The rhizobacteria communities were determined using pyrosequencing of 16S rRNA. In the treatment with phytoremediation species, hydrocarbons 75 g · kg−1soil, and cattle manure 5 g · kg−1soil (T4), there was a significant increase (p<0.05) in rhizobacteria abundance with the highest ASV observed in H. rufa (4980) and the lowest in S. arundinaceum (3955). In the same treatment, bacteria community diversity was high in H. rufa (Chao1, 10310) and the least in S. arundinaceum (Chao 1, 8260) with Proteobacteria, Firmicutes, and Actinobacteria as the dominant phyla. Similarly, in contaminated soil treated with cattle manure, there was a significant increase (p<0.05) in abundance of rhizobacteria genera with Pseudomonas dominating across phytoremediation species. H. rufa was dominated by Bacillus, Fusibacter, and Rhodococcus; G. barbadense was mainly associated with Luteimonas and Mycobacterium, and T. diversifolia was inhabited by Bacillus and Luteimonas. The rhizosphere of O. longistaminata was dominated by Bacillus, Fusibacter, and Luteimonas, while S. arundinaceum was largely inhabited by Sphingomonas. These rhizobacteria genera ought to be applied in the Sudd region for bioremediation.